NOX signaling in molecular cardiovascular mechanisms involved in the blood pressure homeostasis - Santillo, Mariarosaria; Colantuoni, Antonio; Mondola, Paolo; Guida, Bruna; Damiano, Simona (Frontiers in Physiology, 2015)
Blood pressure homeostasis is maintained by several mechanisms regulating cardiac output, vascular resistances and blood volume. At cellular levels, reactive oxygen species (ROS) signaling is involved in multiple molecular mechanisms controlling blood pressure. Among ROS producing systems, NADPH oxidases (NOXs), expressed in different cells of the cardiovascular system, are the most important enzymes clearly linked to the development of hypertension. NOXs exert a central role in cardiac mechanosensing, endothelium-dependent relaxation and Angiotensin-II (Ang-II) redox signaling regulating vascular tone. The central role of NOXs in redox-dependent cardiovascular cell functions renders these enzymes a promising pharmacological target for the treatment of cardiovascular diseases, including hypertension. The aim of the present review is to focus on the physiological role of the cardiovascular NOX-generating ROS in the molecular and cellular mechanisms affecting blood pressure.